Study on the regulation of polythiophene whiskers by electric field induction and the anisotropy of the film surface. Issue 12 (24th August 2021) - Chen, Shuang; Yan, Su; Zhan, Siqi; Wei, Qi; Gao, Lifeng; Li, Zihan; Li, Wei; Yu, Limin; Xu, Tiening; Wang, Shiwei; Zhang, Mingyao
Abstract: In recent years, polythiophene (P3HT) has become a kind of typical conjugated polymer material which is suitable to use on a large scale. However, it is difficult to obtain long P3HT fibers with a highly ordered arrangement due to the entanglement of molecular chains and inherent flexibility. In this work, P3HT fibers were successfully constructed and assembled by an electric‐field‐induced technique, which can be observed directly. The orientation of the P3HT molecules was confirmed by Raman and UV absorption spectra. The excellent anisotropic sliding properties of the surface of the assembled fibers were characterized by the water contact test. This work provides an idea for the preparation of smart sensing materials and lays a foundation for the wider application of P3HT. © 2021 Society of Chemical Industry Abstract : In this work, polythiophene (P3HT) fibers were successfully assembled by an electric‐field‐induced technique. The excellent anisotropic sliding properties of the surface of the assembled fibers were characterized by the water contact test.